Mind the Gaps: Intersex and (Re-productive) Spaces in Disability Studies and Bioethics - Holmes, M. Morgan (Journal of Bioethical Inquiry, 2008)
With a few notable exceptions disability studies has not taken account of intersexuality, and it is principally through the lenses of feminist and queer-theory oriented ethical discussions but not through ‘straight’ bioethics that modes valuing intersex difference have been proposed. Meanwhile, the medical presupposition that intersex characteristics are inherently disabling to social viability remains the taken-for-granted truth from which clinical practice proceeds. In this paper I argue against bioethical perspectives that justify extensive and invasive pre- and post-natal medical interference to eradicate intersex. I argue instead that to constitute the necessary conditions for the recognition of the intersexed child as a person, a life valid in its own right, clinicians must refrain from aggressive interference. Clinical specialists presuppose that intersexed children will be socially disabled and unrecognizable as persons; frustrated by the general failure of traditional interventions to assign a sex, clinicians are now pursuing prenatal technologies, including selective termination, to erase intersex.
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; médecine; premier cycle; queer; sciences; soc2014; thématiques; éthique

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

L'astronomie au féminin - Nazé, Yaël (Vuilbert, 2008)
Qui a découvert un nombre exceptionnel de comètes et d’astéroïdes ? Une femme. Qui a permis d’organiser la population stellaire ? Des femmes. Et la loi permettant d’arpenter d’univers ? Encore et toujours… une femme ! Pourtant, quand il s’agit de citer au hasard un « astronome historique », on pense le plus souvent à des hommes : Galilée, Copernic, ou plus près de nous, Hubble. Certes, au cours des siècles, les femmes n’ont guère eu l’occasion d’accéder aux sciences en général et à l’astronomie en particulier. Est-ce pour autant une raison de croire en l’absence totale de leurs contributions ? À rebours des idées reçues, Yaël Nazé retrace le parcours de quelques scientifiques importantes qui ont en commun une particularité : leur sexe. L’ouvrage suit la trame des grandes découvertes, chaque domaine donnant lieu à une description des phénomènes astronomiques concernés et à un récit où l’on retrouve les grandes figures féminines de l’astronomie
Keywords: astronomie; cours; discipline; fem1000; genre; histoire; histoire et politique; identités LGBTQIA2+; invisibilités; premier cycle; sciences; sciences humaines; thématiques